Free Drying Shrinkage of Wood: A Review - Mingyang Zhao; Lin Yang (BioResources, 2025)
The free drying shrinkage of wood is critical for dimensional stability and industrial applications. This study reviews the influencing factors (drying parameters, environmental conditions, and anatomical structures) and summarizes evaluation indexes and measurement methods. However, current research exhibits significant limitations. Systematic comparisons of free drying shrinkage between softwoods and hardwoods have been lacking, and the mechanism by which internal moisture variations affect shrinkage have remained unclear. Furthermore, existing techniques have failed to simultaneously measure moisture content changes and shrinkage with high accuracy. To address these gaps, future studies should: 1) investigate species-specific free drying shrinkage conditions; 2) elucidate moisture-induced shrinkage mechanisms from macro- and micro-scale perspectives; and 3) develop high-resolution methods for synchronous measurements. Further industrial applications of these findings could optimize wood drying processes and advance wood science and processing technologies.